2019
DOI: 10.3390/met9101128
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Precipitates of IN718 Alloy Fabricated by Selective Laser Melting

Abstract: The microstructure and precipitates of INCONEL 718 alloy (IN718) fabricated by selective laser melting (SLM) are investigated. The matrix is comprised of the elongated γ grains along Z direction, tilting a few degrees. The microstructure mainly consists of a cellular–columnar structure with fine first dendrite arm space of 1–1.5 µm originated from the rapid solidification rate locally. The precipitates of the SLMed IN718 are confirmed to be a significant amount of Laves in the form of irregular bulk distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The microstructure in the bottom region (B) was similar to the top region and is not shown here to avoid repetition. The γ″ and δ particles observed in this study are similar in shape and size (80 ± 34 nm), which have also been observed in the works [7,32,[34][35][36][37][38]. These phases are mostly confined at the bottom and top of the SLM samples by precipitation at the interdendritic zones close to the Laves.…”
Section: Metals 2020 10 X For Peer Reviewsupporting
confidence: 84%
“…The microstructure in the bottom region (B) was similar to the top region and is not shown here to avoid repetition. The γ″ and δ particles observed in this study are similar in shape and size (80 ± 34 nm), which have also been observed in the works [7,32,[34][35][36][37][38]. These phases are mostly confined at the bottom and top of the SLM samples by precipitation at the interdendritic zones close to the Laves.…”
Section: Metals 2020 10 X For Peer Reviewsupporting
confidence: 84%
“…Heat treatment results in the precipitation of strengthening precipitates such as γ'' and δ [28], as well as the dissolution of detrimental phases such as the Laves phase. Since AB specimens were not heat treated, interdendritic Laves phases and carbides were present.…”
Section: Precipitatesmentioning
confidence: 99%
“…This phenomenon could be explained as: ( ) initial cracks existed in the transition region ( Fig. 2(a)) propagated and grew rapidly when the samples were subjected to external load, and these places became the preferential fracture failure sites as a result of stress concentration; ( ) a lack of γ" phase strengthening [41], as well as a weaker ne grain strengthening [44] led by coarser average grain size in transition region, which had been discussed above.…”
Section: Phase and Microstructure Analysismentioning
confidence: 86%
“…The micro-hardness values of 316L region, transition region and Inconel 718 region were measured to be 383.7HV, 303.8HV and 320.7HV, respectively. Compared with the Inconel 718 region, the lower hardness value of the transition region with its microstructure dominated by columnar dendrite grains of Inconel 718 was attributed to the suppression of the γ" phase strengthening [41] caused by the formation of the Laves phase and the segregation of Nb as well as the crack initiation, which had been discussed in Fig. 4(c).…”
Section: Phase and Microstructure Analysismentioning
confidence: 87%
See 1 more Smart Citation